136k views
4 votes
An equation is shown below:

4(2x – 3) = 1

Which of the following correctly shows the first two steps to solve this equation? (1 point)


Step 1: 6x – 7 = 1; Step 2: 6x = 8
Step 1: 6x + 1 = 1; Step 2: 6x = 0
Step 1: 8x – 12 = 1; Step 2: 8x = 13
Step 1: 8x – 3 = 1; Step 2: 8x = 4

2 Answers

1 vote

G'day mate so the answer is Step 1: 8x – 12 = 1; Step 2: 8x = 13

User Matt Harris
by
6.3k points
0 votes
4(2x – 3) = 1
step 1
8x - 12 = 1...expand using distributive property

step 2
8x = 13 ...add 12 to both sides

answer is

Step 1: 8x – 12 = 1; Step 2: 8x = 13 (3rd choice)
User Kert Kukk
by
5.8k points